Acupuncture inhibits reinstatement of intravenous methamphetamine self-administration via gamma aminobutyric acid pathway. Issue 4 (4th March 2020) - Kim, Yo Han; Zhao, Rong Jie; Lee, Soo Min; Kim, Mi Seon; Lim, Sung Chul; Kim, Jae Soo; Lee, Hyun Jong; Yang, Chae Ha; Kim, Hee Young; Lee, Yun Kyu; Lee, Bong Hyo
Abstract : Methamphetamine is one of the widely abused drugs. Nevertheless, there is little predominant therapy for the abuse. In the previous study, acupuncture had shown to attenuate methamphetamine self-administration behavior, and based on, the present study investigated whether acupuncture inhibits the reinstatement of methamphetamine self-administration. As well, a possible neuronal mechanism was investigated. Male Sprague–Dawley rats weighing 270–300 g were trained to intravenously self-administer methamphetamine (0.1 mg/kg) for 3 weeks. Following training, rats who administered stable amount of methamphetamine underwent extinction period of 1 week. Thereafter, priming injection was performed to induce reinstatement, and acupuncture was given immediately before priming. In the second experiment, the selective antagonists of GABAA and GABAB receptors were treated prior to acupuncture to investigate a neuronal mechanism of GABAergic pathway. Acupuncture treatment at HT7, but not at the control acupoint LI5, reduced the active lever responses on the reinstatement session, showing that HT7 suppressed craving for methamphetamine induced by reexposure to the drug during abstinence. And, the effects of acupuncture were blocked by the GABA receptors' antagonists. In addition, HT7 did not influence saline self-administration, indicating that acupuncture effect was selective to the methamphetamine. Results of the present study show that acupuncture at HT7 suppresses reinstatement of methamphetamine self-administration behavior through the GABA receptor system without affecting the normal state. From the results, it may be suggested that acupuncture at HT7 can be a useful option in the treatment of methamphetamine addiction.